The use of GPS horizontals for loading studies, with applications to northern California and southeast Greenland - Wahr, John; Khan, Shfaqat; VAN DAM, Tonie; Liu, Lin; van Angelen, Jan; van den Broeke, Michiel; Meertens, Charles (Journal of Geophysical Research: Solid Earth, 2013)
peer reviewed We describe how GPS measurements of horizontal crustal motion can be used to augment vertical crustal motion measurements, to improve and extend GPS studies of surface loading. We show that the ratio of the vertical displacement to the horizontal displacement, combined with the direction of the horizontal motion, can help determine whether nearby loading is concentrated in a small region (for example, in a single lake or glacier), and where that region is. We illustrate this method by applying it to two specific cases: an analysis of GPS data from northern California to monitor the level of Lake Shasta, and the analysis of data from a single GPS site in southeast Greenland to determine mass variability of two large, nearby outlet glaciers: Helheim Glacier and Midgaard Glacier. The California example serves largely as a proof-of-concept, where the results can be assessed by comparing with independent observations (Lake Shasta tide gauge data, in this case). Our Greenland results show that both Helheim and Midgaard have experienced notable interannual variations in mass loss rate over the last decade. Helheim’s mass loss accelerated rapidly in mid-2003, decelerated in late 2005, and increased again in 2008–2009 before returning to about its pre-2003 rate in late 2010. Midgaard’s mass loss accelerated in mid-2004, and remained more-or-less constant before returning to its pre-2003 rate in late 2008.